Development of Chromium(III) Selective Potentiometric Sensor by Using Synthesized Triazole Derivative as an Ionophore. (12 December 0012) - Kumar, Pankaj; Sharma, Harish Kumar; Shalaan, Kamaal G.
Abstract : A new poly(vinyl chloride) membrane based electrochemical sensor containing synthesized triazole compound, that is, bis-(4-N-amino-5-mercapto-1, 2, 4-triazol-3-yl)alkane (BAMTA) as an electroactive material was prepared and investigated as a chromium(III) selective sensor. The optimum composition of the best performing membrane contained triazole, sodium tetraphenylborate (NaTPB), nitrophenyl octyl-ether (NPOE), and polyvinyl-chloride (PVC) in the ratio 10 : 2 : 50 : 38 w/w. The sensor exhibited near Nernstian slope of 19.8 ± 0.2  mV/decade of activity in the working concentration range of 1.0 × 10 − 5 − 1.0 × 10 − 1  M. It displayed a stable potential response in the pH range 3.4–5.2. The sensor exhibited a fast response time of less than 10 s and could be used for at least 6 weeks without any considerable divergence in potentials. The proposed sensor showed very good selectivity over most of the common cations including Li +, K +, Na +, Ni 2+, Co 2+, Cu 2+, Sr 2+, Ba 2+, Cs +, Pb 2+, Zn 2+, Mg 2+, Cd 2+, Al 3+, Fe 3+, and La 3+ . It could be employed successfully for the determination of Cr(III) ion activity in electroplating and leather tanning industry wastes.